Assessment of Safety, Health and Environment status in Lamerd Cement Factory Based on the European Quality Model (EQFM) - Maysam Bahmani (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The main objective of this research is to evaluate the safety, health and environment status of the Lamerd cement factory based on the European Quality Model (EQFM). This research is an applied and descriptive-analytical survey. The statistical population of this study consists of 26 managers and experts in safety, health and environment at Lamerd Cement Factory. The statistical sample and the sampling method of this study were carried out by non- Probability sampling of the judgment method (census). Research instruments in this study were three researcher-made health assessment, safety assessment, environmental assessment and safety, health and environment assessment standard questionnaire based on EFQM model. The content validity of the data was guided by the supervisor and its reliability was assessed by Cronbach’s alpha method. The reliability was 0.793, 0.719, 0.819, and 0.911, respectively. One-sample t-test was used to analyze the hypotheses test. Friedman test was used to rank variables. SPSS software was used for analysis. In general, based on the tests carried out and the results obtained, we conclude that the safety, health and environment status in Lamerd Cement Factory based on the standard EFQM model is in a good condition. It is suggested to examine the impact of HSE training on employees’ behavior and their environmental culture.